Partners in clime: Public‐private partnerships and British Columbia's capacity to pursue climate policy objectives. (June 2014) - Newman, Joshua; Perl, Anthony
Abstract Governments are increasingly using public‐private partnerships (P3s) to draw the private sector into more active participation in infrastructure development. Climate action initiatives have not typically yielded profitable results for the private sector, and might therefore constrain the placing of conditions by governments on P3 arrangements. This article investigates a major P3 infrastructure project in British Columbia – the Canada Line extension to Vancouver's urban rail transit network – and concludes that the P3 organization did not constrain the government's capacity to pursue policy objectives for climate action. This counterintuitive result occurred because public sector leadership enabled an effective engagement with environmental policy priorities.